(untitled) (Dhaka University Journal of Science, 2022)
The interaction of some divalent metal ions with leucine (leu) and isoleucine (ile) was studied in aqueous solution. Electrochemical techniques like cyclic voltammetry, chronoamperometry and chronocoulometry were used for this study. The electrochemical study demonstrates that the maximum interaction of each metal ion occurs with two deprotonated ligand. The metal ions exchange electrons quasi-reversibly in presence of the ligands and some sort of chemical reaction may be competing with diffusion process at the electrode surface. The current-time and charge-time response accounts for the adsorption of reactant or product or both at the electrode surface. Dhaka Univ. J. Sci. 69(3): 230-237, 2022 (June)